Human Resources and Innovation: Total Factor Productivity and Foreign Human Capital - Claudio Fassio; Sona Kalantaryan; Alessandra Venturini (Institute for the Study of Labor (IZA), 2015)
The objective of this paper is to analyse the role of migrants in innovation in Europe. We use Total Factor Productivity as a measure of innovation and focus on the three largest European countries – France, Germany and the United Kingdom – in the years 1994-2007. Unlike previous research, which mainly employs a regional approach, we analyse the link between migration and innovation at the sectoral level. This allows us to measure the direct contribution of migrants in the sector in which they are actually employed. Moreover, it allows a distinction between the real contribution of migrants to innovation from possible inter-sectoral complementarities, which might as well foster innovation. We control for the different components of human-capital, such as age, education and diversity of origin. To address the possible endogeneity of migration we draw on an instrumental variable strategy originally devised by Card (2001) and adapt it at the sector level. The results show that overall migrants are relevant in all sectors, but some important differences emerge across sectors: highly-educated migrants show a larger positive effect in the high-tech sectors, while middle- and low-educated ones are more relevant in manufacturing. The diversity of countries of origin contributes to innovation only in the services sectors, confirming that in empirical analyses at the regional or national level the diversity measure might capture the complementarity between sectors rather than the contribution of different national skills.
Keywords: F22; F66; O31; O32; 330; migration; innovation; highly skilled migrants; low skilled migrants